Crisis of Natural Resource Governance in Nigeriaas Extractive Industry: Examining the Phenomenon of Artisanal Mining/Quarrying (Global Journal of Human-Social Science, 2015)
This paper examines the phenomenon of artisanal mining/quarrying as a critical manifestation of crisis of natural resources governance in Nigeria. By way of exploratory analysis, predicated on the stakeholder theory of corporate governance, the paper posits that failure of governance in Nigeria's extractive industry has led to unwholesome, unregulated and unsustainable exploitation of natural resources. From the standpoint of the untoward impacts and complications of artisanal mining/quarrying in Nigeria, the paper posits that unregulated exploitation of natural resources poses a threat to economic sustainability, as well as environmental and human security in the country. The paper makes a case for a mutual multistakeholder entrustment system whereby the government synergizes with relevant civil society, community, as well as corporate and non-corporate stakeholders in an effort to bringing about proper governance in the Nigerian mining sector.
Keywords: governance; corporate governance; stakeholder; natural resources(s); artisanal mining/quarrying